Association of TP53 mutations with response and longer survival under immune checkpoint inhibitors in advanced non-small-cell lung cancer. (June 2019) - Assoun, Sandra; Theou-Anton, Nathalie; Nguenang, Marina; Cazes, Aurélie; Danel, Claire; Abbar, Baptiste; Pluvy, Johan; Gounant, Valérie; Khalil, Antoine; Namour, Céline; Brosseau, Solenn; Zalcman, Gérard
Highlights: Frequent smoking-inducedTP53 mutations in NSCLC lead to genetic instability. Genetic instability could drive sensitivity to immunotherapy via neo-antigens. TP53 mutations were found to actually drive longer OS upon immunotherapy. Abstract: Introduction: Tumor mutational burden (TMB) correlates with response to immune checkpoint inhibitors (ICI) in advanced non-small-cell lung cancer (aNSCLC). We hypothesized that TP53 mutations could reflect TMB and be associated with ICI benefit. Methods: TP53 mutations were assessed by next-generation sequencing in aNSCLC patients treated with programmed death-1 (PD-1) blockers. Clinical data, tumor programmed death ligand-1 (PD-L1) expression, and KRAS mutational status were collected. The primary endpoint was overall survival (OS). Results: In total, 72 patients (median [interquartile range] age: 61 [33–83] years) were included; 52 (72%) were male; 39 (54%) had performance status 0–1; 53 (74%) had adenocarcinoma; 20 (28%) received first-line ICI, 52 (72%) second line or more. In 65 patients with available data, 36 (55%) expressed PD-L1 in ≥50% of tumor cells, 20 (31%) in 1–49% of cells, and nine (14%) were PD-L1-negative. Non-synonymous TP53 mutations were observed in 41 (57%) and 25 (35%) harbored KRAS-mutated tumors. After a median follow-up of 15.2 months (95% confidence interval [CI] 10.3–17.4 m), the median OS in the TP53-mutated group was 18.1 months (95% CI 6.6-not reached), vs. 8.1 months (95% CI 2.2–14.5, hazard ratio [HR] = 0.48; 95% CI 0.25-0.95, p = 0.04) in the TP53-wild-type group. Median progression-free survival was significantly longer in TP53-mutated patients (4.5 months, 95% CI 2.8–18.1 versus 1.4, 95% CI 1.1–3.5; p = 0.03), although TP53 mutation status failed to significantly influence PFS in the multivariate analysis (p = 0.32). Objective response rate (ORR) was higher in patients with TP53 mutation (51.2% vs. 20.7%; p = 0.01). In multivariate analysis, TP53 mutations independently associated with longer OS (HR = 0.35, 95% CI 0.16-0.77, p = 0.009). Conclusions: TP53-mutated status correlated with immunotherapy OS benefit in aNSCLC.